COMPORTAMENTO DE CONSUMO EM MEIO A PANDEMIA DA COVID-19 - REGINA CONCEIÇÃO DE ALMEIDA , MÁRCIA; MARLENE SEIDE FROEMMING , LURDES; BEATRIZ NUNES CERETTA , SIMONE (Salão do Conhecimento, 2020)
Jornada de Pesquisa